Managing Expatriates in China A Language and Identity Perspective - Zhang, Ling Eleanor (Palgrave Studies in Chinese Management, 2018)
'Zhang, Harzing and Fan - experts with a genuinely global background and extensive experience - tackle this important topic with an impressive array of research and practical insight. This is a groundbreaking book, essential for anyone studying expatriation in Asia, and China more specifically, and for those considering living there.' -Dr. Yvonne McNulty, Singapore University of Social Sciences, and Founder of Expat Research (expatresearch.com) 'Having researched these issues myself in China and having lived and worked for almost two decades as an expatriate academic in Chinese dominated societies, I can attest to the high relevance and authenticity of the core problem areas dealt with in this volume. And, the concluding recommendations for MNCs, expatriates and local employees are indispensable reading.' -Professor Jan Selmer, Founding Editor-in-Chief, Journal of Global Mobility: The Home of Expatriate Management Research Providing fresh perspectives on managing expatriates in the changing host country of China, this book investigates expatriate management from a language and identity angle. The authors' multilingual and multicultural backgrounds allow them to offer a solid view on the best practices towards managing diverse groups of expatriates, including Western, Indian, and ethnic Chinese employees. With carefully considered analysis which incorporates micro and macro perspectives, together with indigenous Chinese and Western viewpoints, this book explores topics that include the importance of the host country language, expatriate adjustment, ethnic identity confirmation, acceptance and identity. The book presents a longitudinal yet contemporary snapshot of the language, culture, and identity realities that multinational corporation subsidiary employees are facing in China in the present decade (2006-2016). It will thus be an invaluable resource for International Management scholars, those involved in HRM and other practitioners, as well as business school lecturers and students with a strong interest in China. .